KEY STAGES IN THE FORMATION AND DEVELOPMENT OF INTERNATIONAL COOPERATION ON DIGITAL TRADE - Alijonov Ayubjon Qobiljon o‘g‘li (Bright Mind Publishing, 2025)
The development of international cooperation on digital trade has progressed significantly over the past few decades, largely driven by the digitalization of global commerce and the growth of e-commerce. This paper analyzes the key stages in the formation and development of digital trade cooperation among states, particularly focusing on multilateral and bilateral agreements, treaties, and frameworks such as the World Trade Organization (WTO) and regional trade blocs. It examines the legal structures, challenges, and successes of interstate cooperation on digital trade, shedding light on how digital trade regulation is shaping the future of global commerce. This analysis highlights the importance of international collaboration in regulating cross-border data flows, e-commerce, and technology transfer.
Keywords: Digital trade, international cooperation, e-commerce, multilateral agreements, cross-border data flows, WTO, regional trade blocs, trade regulation, technology transfer, global commerce, interstate cooperation, digital commerce, international trade law, trade frameworks, digital economy.